A kind of vinyl chain ferrocene-based covalent organic polymer and its application
By synthesizing ethylene chain ferrocene-based covalent organic polymer ITAFc-COP with a fully conjugated structure, combining photothermal effect and peroxidase-like activity, the problems of antibiotic resistance and biofilm impedance are solved, and the synergistic antibacterial effect on a variety of bacteria is achieved, and good biocompatibility is shown.
Patent Information
- Application Number
- CN202510028113.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-08
AI Technical Summary
Existing antibiotic treatment methods face the problem of antibiotic resistance, and the presence of biofilms reduces the therapeutic effect, and new multimodal therapeutic drugs need to be developed to improve therapeutic effect.
ITAFc-COP, an ethylene chain ferrocene-based covalent organic polymer with a fully conjugated structure, was synthesized through the Knoevenagel reaction, combining photothermal effect and peroxidase-like activity to achieve a synergistic antibacterial effect on Gram-negative bacteria and positive bacteria.
ITAFc-COP has catalase activity in a microacid environment and enhances enzyme activity through photothermal treatment, which has a significant antibacterial effect, and has a low lytic rate of red blood cells and a small impact on cell viability. It is suitable for use in biomedical materials.
Smart Images

Figure CN119431704B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedicine technology, and in particular to a vinyl chain ferrocene-based covalent organic polymer and application thereof. Background Art
[0002] In the history of human social development, the discovery and successful clinical application of antibiotics are regarded as one of the greatest achievements in saving countless lives. However, the evolution of antimicrobial resistance caused by the abuse of antibiotics poses an unprecedented threat to mankind. The antibiotic resistance crisis has led to the emergence of a series of refractory infection-related diseases, such as incurable bacterial infections, diabetic ulcers and sepsis. At the same time, the presence of biofilms can effectively prevent the adhesion of antibiotics to microbial cells, significantly reducing the therapeutic effect. In order to meet contemporary medical challenges, antibiotic-free treatment strategies have become increasingly important due to their efficient therapeutic effects and effective bactericidal ability. However, the formation and existence of biofilms remains a problem that needs to be solved, so the development of anti-infection treatment must be further promoted.
[0003] In recent decades, various therapeutic approaches have been developed as alternatives to antibiotics. Among them, photothermal therapy (PTT) and enzyme therapy are the most attractive approaches to combat biofilm-associated infections due to their remote control, modality compatibility, and site accuracy, avoiding the development of drug resistance. However, the practical application of PTT and enzyme therapy is challenged by the limited efficacy of single-modality treatments. The traditional solution is to develop multimodal therapeutic agents to achieve synergistic amplification of therapeutic effects. To date, many achievements have been made in synergistic sterilization. However, how to rationally design and control the synthesis of multimodal therapeutic agents with minimal side effects and optimal effects remains a challenge.
[0004] Covalent organic polymers (COPs) are a class of booming artificial multifunctional materials, especially covalent organic polymers with extended π-conjugated structures, which have attracted widespread attention as customized materials with targeted applications. In the past few decades, thousands of COPs with different structures and functions have been synthesized. So far, COPs have been shown to be used in, but not limited to, catalysis, photovoltaics, sensing, gas storage, and energy storage. Unlike other artificial porous materials, COPs have an elemental composition similar to that of biological macromolecules. Ferrocene has gradually been used in COPs because the metals it contains have photothermal effects. For example, the patent with application number CN118370819A discloses a covalent organic framework antibacterial material based on polyoxyvanadium, in which ferrocene with double bonds is prepared, and then it is polymerized with amino-modified polyoxyvanadate to obtain a multi-mode combined antibacterial polymer. In addition, there are patents such as application numbers CN116333336A and CN118206706A, which polymerize ferrocene compounds with porphyrin or piperazine to obtain covalent organic polymers. Although the above patents contain conjugated structures, they are not completely conjugated structures. COPs with completely conjugated structures have stronger conjugation effects, which make them have extremely strong light response capabilities. Their antibacterial properties can also be optimized by regulating the main chain structure. For example, by changing the main chain donor capacity to adjust the energy gap of the polymer, it affects its photosensitivity and photodynamic antibacterial properties. In contrast, general conjugated structures may not have all of the above advantages. Therefore, it is necessary to develop a COP with a completely conjugated structure for use in biomedical materials to achieve multi-modal combined antibacterial properties. Summary of the invention
[0005] In view of the above-mentioned prior art, the purpose of the present invention is to provide a vinyl chain ferrocene-based covalent organic polymer and its application. The present invention uses 1,1′-ferrocene dicarboxaldehyde, ethyl bromide and 2,4,6-trimethyl-1,3,5-triazine as monomers, and synthesizes a new COP material ITAFc-COP with a completely conjugated structure through the Knoevenagel reaction, in which the repeated ferrocene units have biological activity similar to peroxidase, and the completely conjugated structure with ITAFc-COP enhances its photothermal activity. ITAFc-COP has both photothermal effect and pod-like activity, and has significant antibacterial effects on both Gram-negative bacteria (G-) and Gram-positive bacteria (G+).
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] The first aspect of the present invention provides a vinyl chain ferrocenyl-based covalent organic polymer, wherein the vinyl chain ferrocenyl-based covalent organic polymer is a covalent organic polymer having a completely conjugated structure obtained by polymerizing 1,1′-ferrocenedic acid dicarboxaldehyde, ethyl bromide and 2,4,6-trimethyl-1,3,5-triazine as monomers.
[0008] Preferably, the vinyl chain ferrocenyl covalent organic polymer is prepared by the following method:
[0009] Under a protective atmosphere, 1,1′-ferrocene dicarboxaldehyde, ethyl bromide and 2,4,6-trimethyl-1,3,5-triazine are added to a mixed solvent and stirred evenly, and a solvent thermal reaction is carried out in a closed environment. The product obtained by filtration is washed and dried to obtain a vinyl chain ferrocene-based covalent organic polymer.
[0010] Preferably, the protective atmosphere is argon.
[0011] Preferably, the molar ratio of 1,1′-ferrocene dicarboxaldehyde, ethyl bromide and 2,4,6-trimethyl-1,3,5-triazine is 3:6:2.
[0012] Preferably, the mixed solvent comprises mesitylene, 1,4-dioxane and trifluoroacetic acid; the volume ratio of mesitylene, 1,4-dioxane and trifluoroacetic acid is 2:2:0.8.
[0013] Preferably, the ratio of the added amount of 1,1′-ferrocene dicarboxaldehyde to the mixed solvent is 0.3 mmol:4.8 mL.
[0014] Preferably, the temperature of the solvent thermal reaction is 150° C., and the time of the solvent thermal reaction is 72 h.
[0015] Preferably, the washing is: washing with dichloromethane, methanol, dimethylformamide and tetrahydrofuran in sequence until the washing liquid is colorless; and the drying is vacuum drying at 120° C. overnight.
[0016] The second aspect of the present invention provides the use of vinyl chain ferrocenyl covalent organic polymers in the preparation of antibacterial drugs.
[0017] The vinyl chain ferrocene-based covalent organic polymer achieves synergistic antibacterial effects through photothermal effect and peroxidase-like activity.
[0018] Preferably, when the concentration of the vinyl chain ferrocenyl covalent organic polymer is 50-300 μg / mL, the hemolysis rate is 0.16±0.09% to 1.21±0.07%.
[0019] Beneficial effects of the present invention:
[0020] (1) The present invention uses 1,1′-ferrocene dicarboxaldehyde, ethyl bromide and 2,4,6-trimethyl-1,3,5-triazine as monomers, and synthesizes a new COP antibacterial material ITAFc-COP with a completely conjugated structure through the Knoevenagel reaction. The repeated ferrocene units have biological activity similar to peroxidase, and the completely conjugated structure with ITAFc-COP makes it have extremely strong photothermal activity and pod-like activity, which can synergistically kill bacteria. It has significant antibacterial effects on both Gram-negative bacteria (G-) and Gram-positive bacteria (G+).
[0021] (2) The ITAFc-COP prepared by the present invention has good catalase activity in a slightly acidic environment and can convert endogenous H2O2 into hydroxyl radicals. The enzyme activity is further increased after photothermal treatment.
[0022] (3) The ITAFc-COP prepared by the present invention produces a good photothermal conversion effect when irradiated with a laser at a wavelength of 638 nm. A 100 μg / mL ITAFc-COP dispersion at 638 nm (1.5 W / cm 2 ) can achieve an ideal photothermal effect within 10 min under the illumination of 400 nm. In addition, ITAFc-COP has high biocompatibility, with a lysis rate of red blood cells lower than 1.21%, little effect on the cell viability of 3T3 cells, and can promote wound healing, which is conducive to its application in the biological field. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : a) Solid-state carbon spectrum of ITAFc-COP 13 C NMR; b) Thermogravimetric curve of ITAFc-COP; c) X-ray diffraction pattern of ITAFc-COP; d) zeta potential of TAFc-COP and ITAFc-COP after the introduction of ion units;
[0024] Figure 2 :a) FT-IR spectra of 1,1′-ferrocenecarboxaldehyde, 2,4,6-trimethyl-1,3,5-triazine and ITAFc-COP; b) FT-IR spectra of TAFc-COP and ITAFc-COP; c) Low-temperature nitrogen absorption / denitrification isotherms of ITAFc-COP at 77 K; d) XPS analysis spectrum of ITAFc-COP; e) High-resolution C1s spectrum of ITAFc-COP; f) High-resolution N1s spectrum of ITAFc-COP; g) High-resolution O 1s spectrum of ITAFc-COP; h) High-resolution Fe2p spectrum of ITAFc-COP; i) High-resolution Br3d spectrum of ITAFc-COP;
[0025] Figure 3 : Characterization of ITAFc-COP, including a) SEM image of ITAFc-COP, scale bar is 1μm; b) SEM image of ITAFc-COP, scale bar is 100nm; c) SEM image of ITAFc-COP, scale bar is 500nm; d) TEM image of ITAFc-COP, scale bar is 1μm; e) TEM image of ITAFc-COP, scale bar is 100nm; f) TEM image of ITAFc-COP, scale bar is 5nm; g) element distribution map of ITAFc-COP; h) distribution of C element in ITAFc-COP; i) distribution of N element in ITAFc-COP; j) distribution of O element in ITAFc-COP; k) distribution of Fe element in ITAFc-COP; l) distribution of Br element in ITAFc-COP;
[0026] Figure 4 :Electron spin resonance spectrum (ESR) of ITAFc-COP;
[0027] Figure 5 :a)The photothermal effect of ITAFc-COP changes with concentration under 638 nm laser irradiation for 10 min; b)The photothermal effect of ITAFc-COP in the concentration range of 0~150 μg / mL (638 nm, 1.5 W / cm -2 , 10 min); (c) infrared thermal images of ITAFc-COP solutions under laser irradiation of different concentrations; d) photothermal effect of ITAFc-COP under 638 nm laser irradiation of different powers; e) photothermal curve of ITAFc-COP (100 μg / mL) under 4 laser repeated on / off cycles; f) temperature change of ITAFc-COP (100 μg / mL) in single cycle heating and cooling; g) negative natural logarithm correlation curve of cooling time and temperature;
[0028] Figure 6 :a) UV-visible spectra of TMB, TMB + H2O2, TMB + ITAFc-COP and ITAFc-COP + TMB + H2O2; b) Effect of 638 nm laser irradiation on the catalytic performance of ITAFc-COP; c) UV-visible spectra of 100 μg / mL ITAFc-COP solution at different pH values; d) UV-visible spectra of ITAFc-COP solutions at different concentrations;
[0029] Figure 7: Concentration gradient sterilization effect diagram of ITAFc-COP, including a) ITAFc-COP + H2O2 + laser sterilization effect diagram, b) plate counting method quantification diagram of ITAFc-COP + H2O2 + laser sterilization;
[0030] Figure 8 : Concentration gradient bactericidal effect diagram of ITAFc-COP, where a) is the colony diagram of Staphylococcus aureus treated under different conditions, b) the quantification diagram of bacterial activity plate count method corresponding to Staphylococcus aureus after different treatments, c) is the colony diagram of Escherichia coli treated under different conditions; d) the quantification diagram of bacterial activity plate count method corresponding to Escherichia coli after different treatments;
[0031] Fig. 9 :a) SYTO9 / PI staining images of Staphylococcus aureus under different treatments; b) SYTO9 / PI staining images of Escherichia coli under different treatments;
[0032] Fig.10 : a) TEM images of Staphylococcus aureus after different treatments; b) TEM images of Escherichia coli after different treatments; the red tip in the figure represents the damage location;
[0033] Fig.11 : Hemolytic effect diagram of different concentrations of ITAFc-COP (n=3, error bars represent standard deviation);
[0034] Fig.12 :ITAFc-COP cytotoxicity assay;
[0035] Fig.13 : Biofilm rate under different treatments;
[0036] Fig.14 :a) Cell scratch test, b) The remaining unmigrated area of cells in each group after scratching;
[0037] Fig.15 :Synthesis route of ITAFc-COP;
[0038] Fig.16 : Wound pictures of mice in each group on days 1, 3, 6, and 9 after treatment;
[0039] Fig.17 :a) Curve of changes in wound healing rate over time in mice (%); b) Curve of changes in mouse body weight during drug administration;
[0040] Fig.18 : H&E and Masson staining images of wound tissues in each group on the 9th day of wound healing (scale bar: 200 μm);
[0041] Fig.19: Organ staining results of each group;
[0042] Fig. 20 : Hematological examination results of treated mice in each group on the 9th day: a) red blood cells of mice on the 9th day; b) white blood cells of mice on the 9th day; c) mean corpuscular volume of mice on the 9th day; d) mean corpuscular hemoglobin of mice on the 9th day; e) hemoglobin of mice on the 9th day; f) red blood cell ratio of mice on the 9th day; g) platelets of mice on the 9th day; h) mean corpuscular hemoglobin concentration of mice on the 9th day. DETAILED DESCRIPTION
[0043] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0044] As introduced in the background technology section, ferrocene compounds contain metallic iron, which gives them photothermal effects. Therefore, more and more research has been conducted on ferrocene covalent organic polymers. However, current ferrocene covalent organic polymers rarely have a completely conjugated structure.
[0045] Based on this, the purpose of the present invention is to provide a ferrocenyl covalent organic polymer based on an ethylene chain and its application. The present invention uses 1,1′-ferrocenyldicarboxaldehyde, ethyl bromide and 2,4,6-trimethyl-1,3,5-triazine as monomers, and synthesizes a new COP material ITAFc-COP with a completely conjugated structure through the Knoevenagel reaction, wherein the repeated ferrocenyl units have biological activity similar to peroxidase, and the completely conjugated structure with ITAFc-COP enhances its photothermal activity; ferrocenyldicarboxaldehyde contains iron ions, which is the basis for ITAFc-COP to have photothermal and Fenton reactions. In addition, ferrocenyldicarboxaldehyde and trimethyltriazine form ethylene bonds through the Knoevenagel reaction, and the triazine has a double bond, so that ITAFc-COP has a completely conjugated structure. Trimethyltriazine and ethyl bromide form quaternary ammonium cations, which adsorb onto the bacterial surface and insert their hydrophobic groups into the lipid layer, changing the permeability of the cell membrane, destroying the membrane structure, leading to leakage of intracellular substances, enzyme or protein denaturation, thereby inhibiting bacterial growth or killing bacteria; making ITAFc-COP have good antibacterial properties. Therefore, ITAFc-COP has both photothermal effect and pod-like activity, and has significant antibacterial effects on both Gram-negative bacteria (G-) and Gram-positive bacteria (G+); ITAFc-COP can effectively promote the healing of infected wounds.
[0046] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0047] 1,1-Ferrocene dicarboxaldehyde and 2,4,6-trimethyl-1,3,5-triazine were purchased from Shanghai Bidex Pharmaceutical Technology Co., Ltd., and ethyl bromide was purchased from Anhui Zesheng Technology Co., Ltd. (Annaiji Chemical);
[0048] Unless otherwise specified, the pH value of PBS used in the present invention is 7.4, and the mass concentration of H2O2 is 30%.
[0049] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.
[0050] Example 1: Preparation of ITAFc-COP
[0051] 2,4,6-Trimethyltriazine (24.63 mg, 0.2 mmol), ethyl bromide (44.78 μL, 0.6 mmol) and 1,1-ferrocenedialdehyde (72.61 mg, 0.3 mmol) were added to a 50 mL round-bottom flask. Subsequently, 1,3,5-trimethylbenzene (2 ml) and 1,4-dioxane (2 ml) were added to the reaction system, and trifluoroacetic acid (0.8 mL) was injected at the same time. The reaction system was ultrasonically treated for 5 minutes, and then argon was bubbled into the reaction system three times to ensure an inert atmosphere. The reaction system was transferred to a high-pressure reactor and reacted at 150 ° C for 72 hours.
[0052] After the reaction is completed, the reaction system is concentrated and cooled to room temperature, filtered, and the precipitate is washed with dichloromethane (DCM), methanol, dimethylformamide (DMF) and tetrahydrofuran (THF) in sequence to remove impurities until the washing liquid is colorless; dried in a vacuum oven at 120°C overnight to obtain a black solid, which is the covalent organic polymer (ITAFc-COP).
[0053] Comparative Example: Preparation of TAFc-COP
[0054] The difference from Example 1 is that ethyl bromide is not added. Finally, TAFc-COP is prepared. The synthesis route is as follows:
[0055] .
[0056] Example 2: Characterization of ITAFc-COP
[0057] (1) Determination of infrared spectrum of catalyst
[0058] Figure 2a) Fourier transform infrared spectroscopy (FT-IR) was used to determine the chemical bonds in ITAFc-COP. It can be seen that the FT-IR spectrum of ITAFc-COP includes triazine (stretching vibration of N-C=N at 1547 cm -1 ), and ferrocene (at 1690 cm -1 , caused by cyclopentadiene). It is worth noting that in ITAFc-COP, the characteristic peak of aldehyde in Fc (C=O vibration at 1680 cm -1 ) almost disappears. Instead, the characteristic absorption peak of the newly formed ethylene bond can also be clearly detected at 1661 cm -1 . Different from the TAFc-COP prepared in the comparative example, a new peak appears in ITAFc-COP at 1097 cm -1 , which is due to the introduction of bromide ion groups, further confirming the successful construction of ITAFc-COP, see Figure 2 b).
[0059] (2) The carbon skeleton structure of ITAFc-COP was further confirmed by solid-state 13 C-NMR. The solid-state 1H-13C NMR spectrum of ITAFc-COP shows strong unsaturated carbon signals including saturated carbon signals and unsaturated carbon signals. As Figure 1 shown in a), the peak at 141.47 ppm is assigned to the unsaturated carbon signal in the triazine ring. The signals at 70.48 and 41.17 ppm belong to unsaturated signals, and these results confirm the successful construction of ITAFc-COP. In addition, Figure 1 d) The successful formation of cationic COP was further confirmed by Zeta potential measurement; different from the negatively charged TAFc-COP (ζ = -13.07 mV), after adding the quaternary ammonium salt unit (ζ = +42.87 mV), the zeta potential increased significantly.
[0060] (3) The permanent porosity of ITAFc-COP was finely detected by 77 K low-temperature nitrogen adsorption analysis. Figure 2 c) The results show that ITAFc-COP exhibits a typical type I adsorption isotherm, with a sharp increase in adsorption amount at low relative pressure (P / P0 < 0.05), and a small hysteresis loop at the branch of the adsorption / desorption curve (0.4 < P / P0 < 0.8), confirming a three-dimensional framework structure dominated by micropores. Based on the non-local density functional theory (NL-DFT) model, the Brunauer - Emmett - Teller (BET) specific surface area of ITAFc-COP was determined to be 694.6 m 2 g -1 , and the main pore diameter is centered at 0.56 nm.
[0061] (4) Figure 2 d) XPS shows that similar to the EDS results, C (83.75 at%), O (13.26 at%), N (1.86 at%), Br (0.46 at%) and Fe (0.68 at%) are present in the ITAFc-COP framework. Figure 2 The C1s peak in e) is deconvoluted into two peaks at 284.8 and 286.53, corresponding to C=C and C=N in the polymer, respectively. Figure 2 f) The N1s spectrum is divided into two peaks at 399.77 and 398.93 eV, which are attributed to the triazine unit. Figure 2 In g), the O 1s peak is deconvoluted into two peaks at 533.51 and 532.19 eV, belonging to the C=O and CO bonds, respectively. Figure 2 h) The high-resolution Fe2p spectrum is divided into two peaks centered at 707.93 and 720.93 eV, which belong to Fe2p 3 / 2 and Fe2p 1 / 2 .also, Figure 2 The XPS peaks of Br 3d at 68.14 and 69.75 eV in i) are attributed to Br - 3D 5 / 2 and 3D 3 / 2 orbital, indicating that bromine is Br - exists in the form of.
[0062] (5) Figure 1 b) shows the thermal stability of ITAFc-COP under N2 atmosphere by thermogravimetric analysis. ITAFc-COP exhibits remarkable thermal stability, with only 31% weight loss at 450°C and more than 54% of its initial mass retained at 800°C.
[0063] (6) If Figure 1 c), the crystallinity and porosity of ITAFc-COP were estimated by powder-X-ray diffraction (PXRD) measurement. The powder X-ray diffraction pattern of ITAFc-COP shows only one broad peak around 25°, indicating the amorphous nature of the synthesized sample.
[0064] (7) Use SEM and TEM to observe the morphology of ITAFc-COP and derive the elemental analysis diagram of ITAFc-COP and the atomic content of various elements. Figure 3 a) ~ Figure 3 c) SEM, Figure 3 d) and Figure 3e) TEM, the morphology and microstructure of ITAFc-COP were comprehensively investigated. These analyses revealed that ITAFc-COP is composed of loosely aggregated spherical particles with particle sizes ranging from nanometers to micrometers. Figure 3 f) High-resolution transmission electron microscopy HR-TEM, the uniform dispersion of micropores can be seen from the contrast between light and dark. Similar to XPS, Figure 3 g) Elemental mapping also shows that C, N, O, Fe, and Br are uniformly distributed in the polymer matrix.
[0065] (8) Photothermal performance of ITAFc-COP
[0066] The morphology of the PD-1 cells was analyzed by varying the concentration of ITAFc-COP (50, 75, 100, 125, 150 µg / mL) or the power density of the laser (0.75, 1.0, 1.25, and 1.5 W / cm 2 ), the photothermal conversion performance of ITAFc-COP was studied in detail. Among them, the preparation method of different concentrations of ITAFc-COP is as follows: weigh 1 mg of ITAFc-COP and use an ultrasonic instrument to fully disperse it in 1 mL of distilled water to prepare a 1 mg / mL mother solution, and then draw 50, 75, 100, 125, and 150 µL from the mother solution and add them to 950, 925, 900, 875, and 850 µL of distilled water, and finally prepare 50, 75, 100, 125, and 150 µg / mL of ITAFc-COP water dispersion. Using pure water as a control, the photothermal conversion performance of ITAFc-COP was 1.5 W / cm 2 , 10 min) to monitor the temperature changes of ITAFc-COP with different concentrations, and the photophysical properties of the synthesized samples were preliminarily studied.
[0067] like Figure 5 As shown in Figure a), unlike the almost constant temperature of pure water, the temperature of the suspension after irradiation for 10 min ranged from 38.5°C to 65.8°C, and the sample concentration varied from 50 to 150 µg / mL. Figure 5 b) The fitting curve of temperature rise and concentration shows a good linear relationship. The calculated R 2 It is 0.996. Figure 5 c) The temperature rise behavior of ITAFc-COP can also be observed intuitively through the changes in the thermal image recorded by the thermal imager. Figure 5 d) When the laser power is increased from 0.75 W cm -2 Increase to 1.5 W cm -2 When the temperature of ITAFc-COP (100 µg / mL) was increased from 26.8℃ to 52.6℃. Figure 5e) During four consecutive heating / cooling cycles, the temperature increase of the ITAFc-COP dispersion remains almost consistent without obvious decay, thus demonstrating the excellent photothermal stability of the synthesized sample.
[0068] Subsequently, in order to quantitatively evaluate the photothermal performance of ITAFc-COP, the photothermal conversion efficiency (η) of ITAFc-COP was calculated. Figure 5 f) and Figure 5 g) shows the τS and θ values in the light-to-heat conversion efficiency calculation formula; Figure 5 g) Temperature dependence of the laser on / off cycle Figure 5 f) The concentration fitting curve shows a good linear relationship, and the R2 value is 0.997. The results show that the η value of ITAFc-COP is 62.38%, and the photothermal conversion efficiency calculation formula is calculated by referring to the photothermal conversion efficiency formula in "A Photothermal-Fenton Reaction Artificial Nanozyme and Its Preparation Method and Application" disclosed in application number CN202310175497.X.
[0069] (9) Peroxidase activity of ITAFc-COP
[0070] The peroxidase activity of ITAFc-COP was studied at different pH. The ROS-generating ability of ITAFc-COP was evaluated using a dual substrate system, i.e., a chromogenic system of H2O2 and 3,3',5,5'-tetramethylbenzidine (TMB), where TMB was used as the chromogenic agent. TMB can be oxidized by ROS to form chromogenic oxTMB. The presence of iron endows ITAFc-COP with the ability to act as an efficient ·OH generator in acidic media.
[0071] The preparation method of TMB used in the experiment is as follows: weigh TMB (3.606 mg, 0.015 mmoL) and dissolve it in 10 mL of ethanol to prepare a 1.5 mmoL / L TMB ethanol solution; the mass concentration of H2O2 used in the experiment is 30%. Take 50 mL of PBS with a pH of 7.4 in a test tube, add phosphoric acid to adjust the pH to 1.5, 2.5, 3.5, 4.5, 5.5 and 6.5 respectively. Preparation of ITAFc-COP with different pH values: Weigh 2 mg of ITAFc-COP and fully disperse it in 2 mL of PBS with different pH values using an ultrasonic device to prepare 1 mg / mL stock solutions with pH values of 1.5, 2.5, 3.5, 4.5, 5.5 and 6.5, respectively. Then, take 100 µL of the stock solutions and add them to 750 µL of PBS with pH values of 1.5, 2.5, 3.5, 4.5, 5.5 and 6.5, respectively. Add 75 µL of TMB and H2O2, respectively, to finally prepare PBS dispersions of ITAFc-COP with a concentration of 100 µg / mL and pH values of 1.5, 2.5, 3.5, 4.5, 5.5 and 6.5, respectively. Preparation of different concentrations of ITAFc-COP: weigh 1 mg of ITAFc-COP and fully disperse it in 1 mL of PBS at pH 5.5 using an ultrasonicator to prepare a 1 mg / mL stock solution. Then, draw 50, 100, 150, and 200 µL of the stock solution and add them to 800, 750, 700, and 650 µL of PBS at pH 5.5, respectively. Then, add 75 µL each of TMB and H2O2 to finally prepare 50, 75, 100, 125, and 150 µg / mL of ITAFc-COP PBS dispersions.
[0072] Ferrocene endows ITAFc-COP with peroxide-mimicking properties, converting H2O2 into toxic hydroxyl radicals (•OH) with bactericidal ability. Therefore, a chemical colorimetric method using 3,3',5,5'-tetramethylbenzidine (TMB) as a probe was used, such as Figure 6 As shown in a), only in the dual matrix system containing both ITAFc-COP and H2O2 can the obvious oxidation UV-visible absorption peak of TMB at 650 nm be observed. It is worth noting that Figure 6 b) Under external laser irradiation, the intensity of the absorption peak is further enhanced, indicating that the pod-like activity can be further enhanced by laser irradiation, exerting an additive therapeutic effect. Figure 6c), the enzyme activity of ITAFc-COP is strongly correlated with the pH of the culture medium, and its color also changes significantly with changes in pH. Specifically, similar to previous reports, as the pH decreases, the simulated pod activity first increases and then decreases, reaching an optimal value at pH 3.5. Even at a pH value similar to the infection microenvironment (pH 5.5), ITAFc-COP also exhibits significant enzyme activity and obvious color changes. At the same time, Figure 6 As shown in (d), the enzyme activity of ITAFc-COP was also positively correlated with the sample dosage. These results reveal the great application prospects of ITAFc-COP in the specific sterilization of infectious microenvironments.
[0073] Test Example 1: In vitro antibacterial test
[0074] (1) Bacterial culture
[0075] This experiment uses two bacteria, Staphylococcus aureus and Escherichia coli, and uses second-generation bacteria to complete the following experiments. The specific culture method of the second-generation bacteria is: first revive the frozen bacteria, thaw the frozen bacteria at 37°C, take 100 µL of the bacterial solution in a shaking tube containing 5 mL of liquid culture medium, place it in a constant temperature shaker (110 rpm, 37°C) and culture it for 12 hours, take 100 µL of the cultured bacterial solution and place it in a 2 mL EP tube containing 900 µL, and then dilute it according to the gradient method according to the gradient of 10 -2 Dilute 5-10 tubes, take 100 µL of the bacterial solution in each tube, use a coating rod to evenly spread it on a culture dish containing solid culture medium, incubate at 37°C for 24 hours, observe the clone morphology and colony count, and take a culture dish with about 1000 colonies as the first generation of bacteria. Use a bacteria picker to pick out a colony from the first generation of bacteria and add it to a shaking tube containing 5 mL of liquid culture medium. Cultivate it according to the method of culturing first generation bacteria to obtain a culture dish with about 1000 colonies as the second generation of bacteria. The specific configuration method of liquid culture medium is: take 5g of LB broth, disperse it in 200 mL of distilled water, and then sterilize it by high pressure sterilization to obtain bacterial liquid culture medium. The specific configuration method of solid culture medium is: take 5g of LB broth and 3g of agar, disperse them in 200 mL of distilled water, and then sterilize them by high pressure sterilization to obtain solid culture medium.
[0076] (2) Determination of antibacterial activity of ITAFc-COP by plate count method
[0077] The preparation method of the dispersion of bacteria in the ITAFc-COP group with different concentrations was as follows: 2 mg of ITAFc-COP powder was fully dispersed in 2 mL PBS to prepare a 1 mg / mL ITAFc-COP stock solution, and 10 µL of 108 CFUmL -1 Bacterial solution (S. aureus or E. coli), then add 990, 940, 915, 890, 865, 840, 790, 740 μL of PBS, then add 50, 75, 100, 125, 150, 200, 250 μL of 1 mg / mL ITAFc-COP stock solution, to obtain ITAFc-COP with concentrations of 0, 50, 75, 100, 125, 150, 200, 250 μL and 10 μL of 1 mg / mL, respectively. 8 CFU mL -1 The mixed solution of PBS dispersion is ITAFc-COP solution.
[0078] The concentrations of ITAFc-COP solutions were 0, 50, 75, 100, 125, and 150 μg / mL, and 10 μL of 30% H2O was added. 2, The ITAFc-COP solutions with different concentrations were irradiated by laser (laser parameters: λ = 638 nm, 1.5 W / cm 2 , 10min)
[0079] Then, the ITAFc-COP solutions of different concentrations were placed in a constant temperature shaker (110 rpm, 37°C) for 12 h, and then the cultured bacterial solution was gradiently diluted 10 5 times, transfer 100 μL of the blown bacterial solution to the solid culture medium and spread it evenly, incubate it at 37°C for 24 h, count the colonies and compare the bacterial activity of each group. Figure 7 a) and Figure 7 b) The antibacterial rates of ITAFc-COP+ H2O2+ laser solution at 150 μg / mL reached 100±0% and 99.84±0.028%, respectively.
[0080] (3) In vitro antibacterial ability of ITAFc-COP under different treatments
[0081] The plate count method was still used to study the antibacterial ability under different treatments, and the bacterial culture was the same as (1). The experiment was divided into eight groups: (I) PBS, (II) PBS + laser, (III) H2O2, (IV) H2O2 + laser, (V) ITAFc-COP, (VI) ITAFc-COP + laser, (VII) ITAFc-COP + H2O2, and (VIII) ITAFc-COP + H2O2 + laser. The preparation method of ITAFc-COP stock solution is: take 2 mg of ITAFc-COP powder, fully disperse it in 2 mL PBS, and prepare it into 1 mg / mL ITAFc-COP stock solution.
[0082] PBS group: add 10 µL of 10 8 CFU mL -1 Bacterial solution was added, and then 990 μL of PBS was added to obtain the PBS group.
[0083] PBS + laser group: add 10 µL 10 8 CFU mL -1 The bacterial solution was then added with 990 μL of PBS, and the dispersion was irradiated with laser to obtain the PBS + laser group.
[0084] H2O2 group: add 10 µL 10 8 CFU mL -1 The bacterial solution was then added with 980 μL of PBS and then with 10 μL of 30 wt% H2O2 to obtain the treated H2O2 group.
[0085] H2O2+ laser group: add 10 µL 10 8 CFU mL -1 The bacterial solution was then added with 980 μL of PBS, followed by 10 μL of 30 wt% H2O2, and the dispersion was irradiated with laser to obtain the treated H2O2+laser group.
[0086] ITAFc-COP group: add 10 µL of 10 8 CFU mL -1 Bacterial solution, then 100 μL of 1 mg / mL ITAFc-COP stock solution was added, and finally 890 μL of PBS was added to obtain the ITAFc-COP group.
[0087] ITAFc-COP+ H2O2 group: add 10 μL 10 8 CFUmL -1 To the bacterial solution, 100 μL of 1 mg / mL ITAFc-COP stock solution, 10 μL of 30 wt % H2O2, and 880 μL of PBS were added to obtain the treated ITAFc-COP+H2O2 group.
[0088] ITAFc-COP+ laser group: add 10 μL 10 8 CFUmL -1 To the bacterial solution, add 100 μL of 1 mg / mL ITAFc-COP stock solution, then add 890 μL of PBS, and finally irradiate the dispersion with a laser to obtain the treated ITAFc-COP+laser group.
[0089] ITAFc-COP+ H2O2+ laser group: add 10μL 10 8 CFUmL -1 To the bacterial solution, add 100 μL of 1 mg / mL ITAFc-COP stock solution, add 10 μL of 30 wt% H2O2, and then add 880 μL of PBS. Finally, irradiate the dispersion with a laser to obtain the treated ITAFc-COP + H2O2 + laser group.
[0090] The laser parameters in the above groups are: λ=638 nm, 1.5 W / cm 2 , 10min.
[0091] Then, the above groups were placed in a constant temperature shaker (110 rpm, 37°C) for 12 h, and then the cultured bacterial solution was gradiently diluted 10 according to the bacterial culture method. 5 Transfer 100 μL of the blown bacterial solution to the solid culture medium and spread it evenly. Incubate at 37°C for 24 h, count the colonies and compare the bacterial activity of each group. Figure 8 a) and Figure 8 As shown in c), the number of colonies treated with (III) H2O2, (IV) H2O2 + laser, (V) ITAFc-COP, and (VII) ITAFc-COP + H2O2 groups was roughly the same as that treated with (I) PBS and (II) PBS + laser, indicating that the bactericidal effect was negligible. The bactericidal effect of ITAFc-COP + laser group (VI) and ITAFc-COP + H2O2 + laser group (VIII) was more obvious, and the number of bacterial colonies was significantly reduced, especially in the ITAFc-COP + H2O2 + laser group, which was attributed to the synergistic effect of enzyme therapy and PTT. At the same time, from Figure 8 b) and Figure 8 d) From the quantitative graph of bacterial activity, it can be seen that the activity of Staphylococcus aureus and Escherichia coli in the ITAFc-COP + laser group was 15.46±0.67% and 16.15±0.49%, respectively; while the activity of Staphylococcus aureus and Escherichia coli in the ITAFc-COP + H2O2 + laser group was 0.77±0.07% and 1.59±0.22%, respectively. This is because ITAFc-COP combines the antibacterial ability of enzyme therapy and PTT to achieve synergistic bactericidal results.
[0092] Test Example 2: Bacterial live / dead staining test:
[0093] SYTO-9 and PI are used to distinguish between live and dead microbial cells. SYTO-9 can penetrate all bacterial membranes (intact and damaged), thus marking the bacteria in green; PI only penetrates the injured bacterial membrane, marking the bacteria in red, while reducing the green color of SYTO-9.
[0094] According to the method in Experiment 1 (3), bacterial suspensions of (I) PBS, (II) H2O2, (III) ITAFc-COP, (IV) ITAFc-COP+H2O2, (V) PBS+laser, (VI) H2O2+laser, (VII) ITAFc-COP+laser, and (VIII) ITAFc-COP+H2O2+laser were prepared. Then, 100 µL of bacterial suspension of each group was mixed with 20 µL SYTO-9 (1.0×10 -3 M) and 20 µL PI (1.5 × 10 - 3 M) and co-incubation was performed for 15 min at 37°C in the dark. After staining, each group was centrifuged in PBS to remove excess SYTO-9 and PI. The bacteria were then resuspended in 50 µL PBS and placed on the surface of the slide. Images of E. coli or S. aureus were then captured using a fluorescent inverted microscope.
[0095] like Fig. 9 As shown, regardless of laser irradiation, E. coli and S. aureus in the PBS group showed vigorous vitality. A similar situation was found for bacteria treated with H2O2, and laser irradiation had little effect on bacterial activity. In contrast, when laser irradiated ITAFc-COP and ITAFc-COP+H2O2, the viability of E. coli and S. aureus decreased significantly at the same time, especially in the ITAFc-COP+H2O2 group, where red fluorescence was significantly enhanced. Specifically, after ITAFc-COP+H2O2+laser treatment, almost all bacteria were labeled with red fluorescence.
[0096] Test Example 3: Bacterial transmission electron microscopy:
[0097] According to the method in Experimental Example 1 (3), bacterial cultures of (I) PBS (control), (II) H2O2, (III) ITAFc-COP, (IV) ITAFc-COP+H2O2, (V) PBS+laser, (VI) H2O2+laser, (VII) ITAFc-COP+laser, and (VIII) ITAFc-COP+ H2O2+laser groups were prepared. Then, 100 μL of bacterial culture of each group was fixed in 2.5 wt% glutaraldehyde solution (4°C, 2 h), washed three times with PBS, embedded in agar and blocked. Then, the bacteria were treated with ethanol solution (30 wt %, 50 wt %, 70 wt %, 90 wt %, 95 wt % and 100 wt %) at room temperature for 10 min to dehydrate them, and then treated with acetone at room temperature for 3 h, embedded with embedding medium (epoxy resin) by gradient infiltration (immersion in acetone and epoxy resin at a mass ratio of 3:1, 1:1, and 1:3 for 1 hour respectively, and finally immersed in pure epoxy resin overnight), negatively stained, and sliced on a nickel grid. The nickel grid was placed under TEM for observation to capture the morphology of bacteria. TEM was used to observe the integrity of the bacterial membranes of different groups of treatments. The morphological changes of bacteria under different treatments were directly observed in the TEM images ( Fig.10 ) It can be seen that the bacterial surface after PBS, H2O2, ITAFc-COP, PBS + laser, and H2O2 + laser treatment remained good, smooth and intact, and the flagella were obvious. However, different degrees of damage were detected in the bacteria treated with ITAFc-COP + laser, ITAFc-COP + H2O2, and ITAFc-COP + H2O2 + laser groups (indicated by red arrows).
[0098] Test Example 4: In vitro biocompatibility test:
[0099] (1) Hemolysis test
[0100] Fresh blood was collected from 5-week-old BALB / c female mice (purchased from Jinan Pengyue Experimental Animal Breeding Co., Ltd.). After centrifugation at 10,000 rpm for 10 minutes, red blood cells were collected and washed with the same amount of PBS until colorless, and the supernatant was discarded. After diluting the red blood cells with PBS at a volume ratio of 3:11, different concentration gradients (50, 100, 150, 200, 300 μg / mL) of ITAFc-COP solution (volume ratio of red blood cell solution: ITAFc-COP solution = 1: 9) were added, incubated at 37°C for 3 hours, and centrifuged at 10,000 rpm for 10 minutes. Then 100 μL of supernatant from each group was placed in a 96-well plate, and the absorbance of each group was measured at 570 nm using an enzyme marker. Distilled water was used as the positive control, and PBS was used as the negative control. The formula for calculating the amount of hemolysis is as follows:
[0101] Hemolysis volume (%) = (A-An) / (Ap-An) × 100%;
[0102] Where "A" is the absorbance obtained by taking the supernatant after adding ITAFc-COP to erythrocytes. "An" is the absorbance obtained by taking the supernatant after adding PBS to erythrocytes (negative control). "Ap" is the absorbance obtained by taking the supernatant after adding distilled water to erythrocytes (positive control).
[0103] like Fig.11 As shown, unlike the positive control experimental group (pure water group) and the negative control experimental group (PBS group), the hemolysis rate of ITAFc-COP in the experimental dose range (50 ~ 300 mg / mL) was 0.16±0.09% ~ 1.21±0.07%, and the hemolysis rate did not exceed 2%, indicating that ITAFc-COP has good blood compatibility and the damage to the red blood cell membrane can be ignored.
[0104] (2) Cytotoxicity assay
[0105] 3T3 mouse embryonic fibroblasts (from the Cell Bank of the Chinese Academy of Sciences) were cultured at 5 × 10 cells per well in a 96-well plate. 3 Cells were seeded at a density of 100 cells per well, 180 µL of cells per well, and 200 µL of PBS was added to the surrounding duplicate wells for liquid sealing to prevent excessive evaporation. After 24 h of incubation, 20 µL of different concentrations (50-150 μg / mL) of ITAFc-COP were added and incubated for 72 h. Then 20 µL of MTT (4 mg / mL) solution was added to each well and incubated in the incubator for 4 h. After 4 h, the supernatant was aspirated and 150 µL of dimethyl sulfoxide was added to dissolve MTT (tetramethylthiazolyl blue). After dissolving on a shaker for 10 min, the absorbance of the 96-well plate was measured at 570 nm using a microplate reader. Each set of experiments was repeated three times.
[0106] At the same time, in order to further study the adverse damage of the material itself to normal cells, the cytotoxicity test of ITAFc-COP on 3T3 mouse embryonic fibroblasts was carried out. Fig.12 The cell viability of 3T3 mouse embryonic fibroblasts cultured for 3 days with different concentrations of ITAFc-COP (50-150 μg / mL) is shown. The relative viability of NIH 3T3 cells gradually increased with decreasing concentrations of the substance. However, even at a high sample dose of 150 μg / mL, the viability of NIH 3T3 cells remained above 80%, all of which confirm that ITAFc-COP, with good biocompatibility, is a selective agent for bacteria.
[0107] (3) Biofilm experiment
[0108] In order to evaluate the anti-biofilm effect of ITAFc-COP, 150 μL of Staphylococcus aureus (second-generation bacterial stock solution, culture method see Test Example 1 (1)) was added to 3 wells in each group of 96-well plates, and a Staphylococcus aureus biofilm model was established after incubation for 48 hours. The experiment was divided into seven groups: (I) PBS (control), (II) ITAFc-COP, (III) H2O2, (IV) H2O2+laser, (V) ITAFc-COP+H2O2, (VI) ITAFc-COP+laser, (VII) ITAFc-COP+H2O2+laser; 50 μL of PBS, H2O2 or 100 μg / mL ITAFc-COP solution was added to each group and irradiated (638 nm, 1.5 W / cm 2 , 10 min). The suspended bacteria and materials were washed with PBS, then fixed with formaldehyde (150 μL), stained with crystal violet (0.1%, 5 μL), decolorized with acetic acid (100 μL), and finally measured for absorbance. Each step took 30 minutes, and was washed three times with PBS between each step. After the operation, quantitative analysis was performed using crystal violet staining (CV) ( Fig.13 ) It can be seen that, unlike the PBS and ITAFc-COP treatment groups, which had smaller color changes, the other treatment groups had obvious color changes, especially the ITAFc-COP+H2O2+laser group. At the same time, the UV absorbance also showed that ITAFc-COP+H2O2+laser had a significant effect in eliminating biofilm biomass, but its UV absorbance was much weaker than that of other groups. The biofilm removal rate of the ITAFc-COP+H2O2+laser group reached 59.59±4.96%, which was higher than that of the other groups (ITAFc-COP group 12.87±2.84%, H2O2 group 16.69±1.36%, H2O2+laser group 19.36±2.64%, ITAFc-COP+H2O2 group 31.86±5.66%, ITAFc-COP+laser group 42.07±3.01%). These results indicate that the photothermal synergistic effect of ITAFc-COP significantly inhibited the growth of biofilm.
[0109] (4) Cell scratch test
[0110] Mouse NIH 3T3 fibroblasts (from the Cell Bank of the Chinese Academy of Sciences) were inoculated in 6-well plates and cultured for 24 hours. They were then scraped with the tip of a sterile pipette and washed twice with PBS. 1 mL of mitomycin was added to each well and removed after 1 hour of culture. Mitomycin was treated with ITAFc-COP and PBS, respectively. Cell healing was observed under a microscope at 0, 12, and 24 hours. ImageJ software was used to measure the distance of cell migration and calculate the percentage of wound healing. PBS was used as the control. Fig.14a) The effect of different doses (0-150 μg / mL) of ITAFc-COP on the migration ability of NIH 3T3 cells over time (0, 12, and 24 h) was estimated by cell scratch assay. It can be seen that different doses of ITAFc-COP (0-150 μg / mL) had little effect on cell migration. Fig.14 b) After 12 h of co-incubation, the wound areas at 0, 50, 75, 100, 125, and 150 μg / mL increased to 30.66±1.39%, 27.08±1.93%, 26.51±0.70%, 25.80±1.16%, 23.12±1.42%, and 24.88±0.75%, respectively. After 24 h, ITAFc-COP had little adverse effect on the migration activity of normal cells, with the migration areas being 46.88±0.77%, 45.88±1.50%, 45.53±0.37%, 44.55±1.00%, 43.59±0.63%, and 40.33±0.61%, respectively. All these results indicate that ITAFc-COP has good biosafety and can be used as a biocompatible therapeutic agent to combat bacterial infections.
[0111] Test Example 5:
[0112] (1) In vivo wound healing experiment
[0113] Five-week-old BALB / c mice (purchased from Jinan Pengyue Experimental Animal Breeding Co., Ltd.) were randomly divided into 7 groups: I) PBS (control), II) ITAFc-COP, III) H2O2, IV) H2O2+laser, V) ITAFc-COP+H2O2, VI) ITAFc-COP+laser, and VII) ITAFc-COP+H2O2+laser, with 6 mice in each group. Before surgery, the back of each mouse was shaved to form a 5 mm wound, and then infected with Staphylococcus aureus (1×10 6 CFU / mL) for 24 hours to establish the wound healing model. The mice were treated according to the requirements of different group settings, and the wound surface of each group of mice was recorded on the 1st, 3rd, 6th, and 9th days, and the changes in body weight were monitored. The changes in wound size were measured using an image analysis program (Image.J).
[0114] like Fig.16 As shown in Figure 2, even in the absence of treatment (PBS group), the wounds on the back of the mice gradually healed over time. However, there were significant differences between the treated groups and the untreated groups, especially compared with the ITAFc-COP+H2O2+laser group. Fig.17As shown in a), on the 9th day, the wound contraction rates were 49.61±1.77% in the PBS group, 53.52±0.60% in the ITAFc-COP group, 52.83±3.42% in the H2O2 group, 55.52±0.94% in the H2O2+laser group, 57.86±0.16% in the ITAFc-COP+H2O2 group, 66.1±1.76% in the ITAFc-COP+laser group, and 77.35±2.58% in the ITAFc-COP+H2O2+laser group. It is worth noting that compared with the PBS group, there was no significant improvement in wound healing in the ITAFc-COP and H2O2 groups with / without laser irradiation. On the contrary, the ITAFc-COP+H2O2 group had a greater difference, among which the ITAFc-COP+laser treatment had a more direct effect and significantly reduced wounds. Among them, the ITAFc-COP+H2O2+laser group, in which photothermal and enzyme treatments were performed simultaneously, had the best wound healing effect. These results suggest that ITAFc-COP significantly promotes the wound healing process. Fig.17 As shown in b), the body weight of mice in each group increased slowly, and there was no significant difference among the groups, confirming that ITAFc-COP has low toxicity and has no adverse effects on mouse growth.
[0115] (2) Tissue staining experiment
[0116] Histological analysis using hematoxylin and eosin (H&E) and Masson staining was performed to directly evaluate the healing of skin tissue after 9 days of treatment. Fig.18 As shown, both the PBS and H2O2 treatment groups showed obvious inflammatory cells, and the skin epidermis was incomplete regardless of laser irradiation. In contrast, the ITAFc-COP treatment group showed varying degrees of skin structure regeneration. The ITAFc-COP+H2O2+laser group had the most significant effect in promoting wound healing, with visible blood vessels, collagen fibers, and a naturally mature epidermal layer, indicating that the wound was completely healed.
[0117] In addition, histological sections were collected and H&E staining was performed to evaluate the damage to internal organs (heart, liver, spleen, lung, and kidney) in different groups. Fig.19 As shown in the figure, no abnormal lesions or inflammatory manifestations were found in the main organs, and no histological changes were found. These results confirm that ITAFc-COP has good biosafety in vivo.
[0118] (3) Routine blood test
[0119] On day 9, approximately 2 mL of blood was collected from the ophthalmic artery of the mice, and each sample was subjected to routine blood tests. Fig. 20 It can be seen that all blood parameters were within the normal range, indicating that ITAFc-COP has good biosafety.
[0120] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A vinyl chain ferrocenyl covalent organic polymer, characterized in that: The vinyl chain ferrocenyl-based covalent organic polymer is a covalent organic polymer with a completely conjugated structure obtained by polymerizing 1,1′-ferrocenedicarbaldehyde, ethyl bromide and 2,4,6-trimethyl-1,3,5-triazine as monomers.
2. The vinyl chain ferrocenyl covalent organic polymer according to claim 1, characterized in that: The vinyl chain ferrocenyl covalent organic polymer is prepared by the following method: Under a protective atmosphere, 1,1′-ferrocene dicarboxaldehyde, ethyl bromide and 2,4,6-trimethyl-1,3,5-triazine are added to a mixed solvent and stirred evenly, and a solvent thermal reaction is carried out in a closed environment. The product obtained by filtration is washed and dried to obtain a vinyl chain ferrocene-based covalent organic polymer.
3. The vinyl chain ferrocenyl covalent organic polymer according to claim 2, characterized in that: The protective atmosphere is argon.
4. The vinyl chain ferrocenyl covalent organic polymer according to claim 2, characterized in that: The molar ratio of the 1,1′-ferrocene dicarboxaldehyde, ethyl bromide and 2,4,6-trimethyl-1,3,5-triazine is 3:6:
2.
5. The vinyl chain ferrocenyl covalent organic polymer according to claim 2, characterized in that: The mixed solvent includes mesitylene, 1,4-dioxane and trifluoroacetic acid; the volume ratio of mesitylene, 1,4-dioxane and trifluoroacetic acid is 2:2:0.
8.
6. The vinyl chain ferrocenyl covalent organic polymer according to claim 2, characterized in that: The ratio of the added amount of the 1,1′-ferrocene dicarboxaldehyde to the mixed solvent is 0.3 mmol:4.8 mL.
7. The vinyl chain ferrocenyl covalent organic polymer according to claim 2, characterized in that: The temperature of the solvent thermal reaction is 150° C., and the time of the solvent thermal reaction is 72 hours.
8. The vinyl chain ferrocenyl covalent organic polymer according to claim 2, characterized in that: The washing step is: washing with dichloromethane, methanol, N,N-dimethylformamide and tetrahydrofuran in sequence until the eluate is colorless; and the drying step is vacuum drying at 120° C. overnight.
9. Use of the vinyl chain ferrocenyl covalent organic polymer according to any one of claims 1 to 8 in the preparation of antibacterial drugs.
10. The use according to claim 9, characterized in that: When the concentration of the vinyl chain ferrocenyl covalent organic polymer is 50-300 μg / mL, the hemolysis rate is 0.16±0.09% to 1.21±0.07%.
Citation Information
Patent Citations
A photothermal-Fenton-like artificial nanozyme, its preparation method and application
CN115845086B
Ferrocene-based metal organic framework material as well as preparation method and application thereof
CN116333336A
Antibacterial material for realizing sterilization by utilizing and improving infected microenvironment as well as preparation method and application of antibacterial material
CN118206706A
Polyoxyvanadium-based covalent organic framework antibacterial material
CN118370819A
Ferrocenyl three-dimensional covalent organic framework material and preparation method thereof
CN114853968A